DETERMINATIONOFTHETEMPERATUREANDDENSITYOF ELECTRON OFGLOWDISCHARGE IN NITROGENBYUSINGOPTICALEMISSIONSPECTROSCOPY - A. Khadayeira, Abdulhussain; M.Taher, Wessam (Al-Qadisiyah Journal of Pure Science, 2019)
In this paper a hollow cylindrical cathode (HC)was used as a source of glowing discharge plasma at low pressure.The optical description of the system was done by recording emission spectrum for wavelengths emitted from plasma in spectral range (190-1000) nm, then analyzing this spectrum. Finally,the electron temperature and plasma density wereexamined by employing a spectroscopy. The electron temperature was measured throughcalculating approximatelyintensity’s ratio of two lines.Via the conditions that the inner cylinder diameter was R = (3&6) cm; HCD supply voltage, (300-900) V.Also, a study of effect of gas pressure and voltage change along plasma discharging was done and the temperature of electron for plasma estimated spectrally between (0.8-1.3) eV and the density of electrons (2.8x1015-7x1017) cm-3